Direct and label‐free detection of the human growth hormone in urine by an ultrasensitive bimodal waveguide biosensor. Issue 1 (27th September 2016) - González‐Guerrero, Ana Belén; Maldonado, Jesús; Dante, Stefania; Grajales, Daniel; Lechuga, Laura M.
Abstract : A label‐free interferometric transducer showing a theoretical detection limit for homogeneous sensing of 5 × 10 –8 RIU, being equivalent to a protein mass coverage resolution of 2.8 fg mm –2, is used to develop a high sensitive biosensor for protein detection. The extreme sensitivity of this transducer combined with a selective bioreceptor layer enables the direct evaluation of the human growth hormone (hGH) in undiluted urine matrix in the 10 pg mL –1 range. Abstract : Graphical abstract of the hGH direct detection using a bimodal nanometric waveguide in which anti‐hGH are immobilizing on by a silane coupling agent.